DOP09 Mirikizumab-induced transcriptome changes in patient biopsies at Week 12 are maintained through Week 52 in patients with Ulcerative Colitis. (27th May 2021) - Johnson, T; Steere, B; Zhang, P; Zang, Y; Higgs, R; Gottlieb, K; Reinisch, W; Panés, J; Krishnan, G
Abstract: Background: Mirikizumab (miri), an anti-IL-23p19 monoclonal antibody, demonstrated efficacy and was well-tolerated in a phase 2 randomised clinical trial in patients with moderate-to-severe ulcerative colitis (UC; NCT02589665). After 12 weeks (W) of treatment, miri was shown to down-regulate several transcripts correlated with increased UC disease activity as well as anti-TNF resistance. Here we show W52 gene expression analysis from the induction responder cohort at W12 for both miri and PBO treated patient biopsy samples to identify sustained changes in gene expression. Methods: Miri-treated patients who achieved clinical response (decrease in 9-point Mayo subscore [rectal bleeding, stool frequency, endoscopy] of ≥2 points and ≥35% from baseline [BL] with either a decrease of RB subscore of ≥1 or an RB subscore of 0 or 1) or better at W12 were re-randomised to miri 200 mg administered subcutaneously (SQ) every 4 weeks or every 12 weeks through W52. Patients given placebo (PBO) in induction who achieved clinical response continued on PBO in the maintenance period. Colonic biopsies were obtained at W0, 12, and 52 from the most affected area at least 30 cm from the anal verge (miri N=31, PBO N=7). Transcript changes at W12 from BL in the PBO and miri arms were clustered into differentially expressed genes (DEGs) using the Bayesian Limma R-package. Among these DEGs, similarly expressed genes (SEGs) were identified as those which maintained their W12 expression level through W52. Results: Analysis of transcript changes in W12 responders who continued to maintenance identified a profile of DEG-SEGs in responders (Fig 1A). Of these genes, 63 (70.8%) were present only in miri responders, 5 (5.6%) were present only in PBO responders, and 21 (23.6%) were present in both groups (Fig 1B, C). The magnitude of transcript changes was greater at W12, and more consistent through W52, in the group of miri responders compared to PBO responders (Fig 2). A separate cluster of DEG-SEGs correlated with to disease activity indeces (Robarts Histopathology Index [RHI], modified Mayo; both r>0.5) were shown to be sustained in the miri treated patients but not in the placebo patients. Conclusion: In this limited sample of W12 PBO and miri responders, miri responders showed broader, larger, and more sustained magnitude of changes at W52 compared to PBO responders. The qualitative description of transcripts suggests a distinct molecular healing pathway associated with miri treatment, as compared to the spontaneous healing that occurred in PBO responders. A cluster of transcripts that correlated with disease activity indices was identified, demonstrating consistency across molecular, endoscopic and clinical indices of healing in UC.